2021
DOI: 10.1007/s11252-020-01080-5
|View full text |Cite
|
Sign up to set email alerts
|

The resilient frugivorous fauna of an urban forest fragment and its potential role in vegetation enrichment

Abstract: Anthropocentric defaunation affects critical ecological processes, such as seed dispersal, putting ecosystems and biomes at risk, and leading to habitat impoverishment. Diverse restoration techniques could reverse the process of habitat impoverishment. However, in most of the restoration efforts, only vegetation cover is targeted. Fauna and flora are treated as isolated components, neglecting a key component of ecosystems' functioning, the ecological interactions. We tested whether the resilient frugivorous ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 112 publications
1
8
0
1
Order By: Relevance
“…We also found that the top three frugivore birds were medium-and large-size omnivorous generalist birds (Table 2), consistent with some studies in disturbed habitats [11,14,73] and some studies on bird composition in urban ecosystems [74,75], they occupy a dominant position in both urban plant-frugivore networks and urban bird communities. They have a wider feeding niche and eat more plant fruits [11]. Moreover, their high adaptability to urban high disturbance habitats makes them dominant in the overall number [76], which may increase the cumulative connection of plant-frugivore bird networks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that the top three frugivore birds were medium-and large-size omnivorous generalist birds (Table 2), consistent with some studies in disturbed habitats [11,14,73] and some studies on bird composition in urban ecosystems [74,75], they occupy a dominant position in both urban plant-frugivore networks and urban bird communities. They have a wider feeding niche and eat more plant fruits [11]. Moreover, their high adaptability to urban high disturbance habitats makes them dominant in the overall number [76], which may increase the cumulative connection of plant-frugivore bird networks.…”
Section: Discussionsupporting
confidence: 90%
“…The process of urbanization is accompanied by the loss and fragmentation of habitat and urban bird richness, the decrease in diversity, and the homogenization and domination of urban bird communities by generalist species [9][10][11][12]. The connectivity between patches decreases, and the filtering effect of the landscape scale leads to a change in the bird community [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these species contribute to the stability of the network against possible disturbances, increasing its robustness (Bascompte et al 2003, Saavedra et al 2011, Silva et al 2015, Carlo & Morales 2016, Palacio et al 2016, Ramos-Robles et al 2018b. Considering the natural history of these birds, it is important to mention that Silver-beaked Tanager is an abundant species that forages in flocks and often occupies the vegetation border and altered areas (Lasky & Keitt 2012, Silva et al 2015, Rigacci et al 2021. Therefore, from a functional perspective, this species can be an important component in the regeneration of degraded areas.…”
Section: Discussionmentioning
confidence: 99%
“…This plantation is approximately 60 years old [ 45 ], where no thinning operations have been made, and is characterized by a very uniform structure, the predominant species being J. neotropica , mainly mixed with tree species of Cedrela montana , Siparuna muricata , Inga fendleriana , Vibumum triphyllum , Streptosolen jamesonii , Palicourea heterochroma and Oreopanax rosei [ 45 ]. The species is cultivated because it is an important timber species that produces high quality wood [ 46 ], and its nuts are edible and used as a colorant in the textile industry [ 47 ].…”
Section: Methodsmentioning
confidence: 99%